American visceral leishmaniasis: Factors associated with lethality in the state of São Paulo, Brazil - Madalosso, Geraldine; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Ribeiro, Ana Freitas; Cruz, Lisete Lage; Nogueira, Péricles Alves; Lindoso, José Angelo Lauletta (Hindawi, 2012)
Objectives. To identify factors associated with death in visceral leishmaniasis (VL) cases. Patients and Methodology. We evaluated prognostic factors for death from VL in São Paulo state, Brazil, from 1999 to 2005. A prognostic study nested in a clinical cohort was carried out by data analysis of 376 medical files. A comparison between VL fatal cases and survivors was performed for clinical, laboratory, and biological features. Association between variables and death was assessed by univariate analysis, and the multiple logistic regression model was used to determine adjusted odds ratio for death, controlling confounding factors. Results. Data analysis identified 53 fatal cases out of 376 patients, between 1999 and 2005 in São Paulo state. Lethality was 14.1 (53/376), being higher in patients older than fifty years. The main causes of death were sepsis, bleeding, liver failure, and cardiotoxicity due to treatment. Variables significantly associated with death were severe anemia, bleeding, heart failure, jaundice, diarrhea, fever for more than sixty days, age older than fifty years, and antibiotic use. Conclusion. Educational health measures are needed for the general population and continuing education programs for health professionals working in the affected areas with the purpose of identifying and treating early cases, thus preventing the disease evolution towards death. © 2012 Geraldine Madalosso et al.
Keywords: antibiotic agent; antiprotozoal agent; aspartate aminotransferase; bilirubin; blood derivative; immunosuppressive agent; adolescent; adult; age; anemia; antibiotic therapy; aspartate aminotransferase blood level; asthenia; bilirubin blood level; bleeding; Brazil; cardiotoxicity; child; clinical feature; cohort analysis; confounding variable; congestive heart failure; controlled study; coughing; data analysis; death; dehydration; diabetes mellitus; diarrhea; drowsiness; drug fatality; dyspnea; edema; fatality; febrile neutropenia; fever; heart arrhythmia; heart failure; human; hypoalbuminemia; infant; jaundice; laboratory test; lethality; liver disease; liver failure; major clinical study; medical record; multivariate logistic regression analysis; opportunistic infection; pallor; peripheral vascular disease; pneumonia; preschool child; priority journal; prognosis; risk; risk factor; school child; sepsis; splenectomy; survivor; thrombocytopenia; tuberculosis; univariate analysis; visceral leishmaniasis; vomiting